Preparation method of new energy automobile data connection wire harness
By oxidizing, grafting and nickel-plating the carbon fiber and combining it with polyphenylene sulfide-based composite material coating, the problem of insufficient electromagnetic shielding in the data connection harness of new energy vehicles was solved, and efficient electromagnetic shielding and vibration resistance were improved.
Patent Information
- Application Number
- CN202511130230.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-09-19
- Estimated Expiration
- 2045-08-13
AI Technical Summary
The electromagnetic shielding performance of existing new energy vehicle data connection harnesses is insufficient, resulting in the intrusion of electromagnetic interference sources, affecting the reliability of vehicle control modules and intelligent driving systems.
By oxidizing carbon fiber, grafting silane coupling agent and 4,4'-diaminodiphenyl sulfide, and then nickel-plating, modified carbon fiber is formed, and then coated with polyphenylene sulfide-based composite materials to construct a continuous conductive network, enhance electromagnetic shielding effectiveness, and reduce electromagnetic wave reflection.
It significantly improves the electromagnetic shielding effectiveness, reduces electromagnetic wave reflection, enhances the vibration resistance of the connecting harness, and ensures the reliability of the vehicle control module and intelligent driving system.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy vehicles, and in particular, relates to a method for preparing a data connection harness for a new energy vehicle. Background Art
[0002] As the core transmission carrier of the vehicle's electrical system, the electromagnetic shielding performance of the data connection harness of new energy vehicles is directly related to the vehicle's electromagnetic compatibility and the reliability of electronic equipment. With the development of electrification and intelligence of automobiles, there are more and more electronic equipment on the vehicle, and the signal transmission frequency is also getting higher and higher, resulting in a significant increase in the number and intensity of electromagnetic interference sources. The electromagnetic shielding performance of the automotive data connection harness in the existing technology can no longer meet the use requirements of new energy vehicles. When the shielding effectiveness is insufficient, external interference can invade the harness through capacitive coupling, causing controller LAN bus signal delay, amplitude jump and timing disorder, resulting in vehicle control module false alarm code or function failure, especially high-frequency video signals are more susceptible to interference, causing image distortion or interruption, which directly affects the reliability of the intelligent driving system. In order to solve the above technical defects, the present invention provides a preparation method for a new energy vehicle data connection harness. Summary of the Invention
[0003] The object of the present invention is to provide a method for preparing a data connection harness for a new energy vehicle, so as to solve the problems mentioned in the above background technology.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a new energy vehicle data connection harness comprises the following steps: In the first step, the surface sizing agent of the carbon fiber is removed and the carbon fiber is oxidized to obtain oxidized carbon fiber.
[0005] In the second step, a silane coupling agent is grafted onto the surface of the oxidized carbon fiber, and then reacted with 4,4'-diaminodiphenyl sulfide to obtain functionalized carbon fiber.
[0006] The third step is to nickel-plate the surface of the functionalized carbon fiber and then perform heat treatment to obtain the modified carbon fiber.
[0007] The fourth step is to wrap the modified carbon fiber around the wire core, and then melt-extrude the polyphenylene sulfide-based composite material and wrap it around the outside of the wire core wrapped with the modified carbon fiber to obtain the new energy vehicle data connection harness.
[0008] As a further preferred embodiment of the present invention, the steps for preparing the oxidized carbon fiber are: A Soxhlet extractor is used to remove the sizing agent on the surface of the carbon fiber. The extraction solvent is acetone, the extraction temperature is 40-60°C, and the extraction time is 12-24 hours. After the extraction, the carbon fiber is taken out and washed with anhydrous ethanol and deionized water in sequence and then dried. The extracted and dried carbon fiber, silver nitrate, potassium persulfate, and deionized water are then mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the mixture is stirred at a temperature of 70-80°C for 3-4 hours. After the reaction is completed, the solid is filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried to obtain oxidized carbon fiber.
[0009] As a further preference of the present invention, the preparation steps of the functionalized carbon fiber are: The oxidized carbon fiber, silane coupling agent and toluene are mixed in a reaction bottle equipped with a condenser, a thermometer and a magnetic stirring rotor, and the magnetic stirring is turned on and the reaction is carried out at a temperature of 60 to 100 ° C for 8 to 16 hours. After the reaction is completed, the oxidized carbon fiber is filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried. The oxidized carbon fiber, 4,4'-diaminodiphenyl sulfide and toluene after the reaction and drying are mixed in a reaction bottle equipped with a condenser, a thermometer and a magnetic stirring rotor, and the magnetic stirring is turned on and the reaction is carried out at a temperature of 30 to 60 ° C for 2 to 4 hours. After the reaction is completed, the oxidized carbon fiber is filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried to obtain functionalized carbon fiber.
[0010] As a further preference of the present invention, the preparation steps of the modified carbon fiber are: The functionalized carbon fiber is immersed in a palladium chloride solution for 1 to 2 minutes and then added to an aqueduct. The plating solution in the aqueduct contains a nickel source, a reducing agent, a chelating agent and ammonia water, and the plating solution is preheated to 70 to 90°C. The nickel plating time is 20 to 60 minutes. After the nickel plating is completed, the functionalized carbon fiber is taken out and washed with deionized water and then dried. Thereafter, it is heated to 200 to 300°C under nitrogen protection conditions and kept warm for 40 to 120 minutes to obtain a modified carbon fiber.
[0011] As a further preferred embodiment of the present invention, the preparation steps of the new energy vehicle data connection harness are as follows: The modified carbon fiber is wrapped around the wire core, and polyphenylene sulfide, nylon 66, compatibilizer, modified glass fiber, polytetrafluoroethylene powder, and antioxidant are mixed and added into a twin-screw extruder for melt extrusion and then wrapped around the outside of the wire core wrapped with the modified carbon fiber to obtain a new energy vehicle data connection harness.
[0012] As a further preference of the present invention, the preparation steps of the modified glass fiber are: Glass fiber, silane coupling agent, and toluene are mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction is carried out at a temperature of 60 to 100° C. for 6 to 12 hours. After the reaction is completed, the glass fiber is filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried to obtain modified glass fiber.
[0013] As a further preferred embodiment of the present invention, the silane coupling agent is KH-560.
[0014] As a further preferred embodiment of the present invention, the nickel source is nickel sulfate, the reducing agent is at least one of dimethylamine borane and sodium hypophosphite, and the complexing agent is at least one of sodium citrate and sodium malate.
[0015] As a further preferred embodiment of the present invention, the antioxidant is at least one of antioxidant 1010, antioxidant 1035, sodium hypophosphite, and antioxidant 168.
[0016] As a further preferred embodiment of the present invention, the compatibilizer is ethylene-glycidyl methacrylate copolymer (EGMA).
[0017] As a further preferred embodiment of the present invention, the temperature condition for melt extrusion is 290 to 300°C.
[0018] The present invention has at least one of the following beneficial effects: The present invention functionalizes carbon fibers and grafts amino and thioether structures with good coordination ability onto the surface of the functionalized carbon fibers. These structures can provide stable nucleation sites, reduce the nucleation energy barrier, promote uniform nucleation, and enhance the bonding ability between the functionalized carbon fibers and the coating, significantly improving the coverage and density of the coating, constructing a continuous and efficient conductive network, significantly improving the conductivity, and thereby significantly enhancing the electromagnetic shielding effectiveness of the modified carbon fibers.
[0019] Carbon fiber itself has good electromagnetic shielding performance, but its high conductivity will cause significant electromagnetic wave reflection, leading to secondary electromagnetic pollution. The modified carbon fiber of the present invention is grafted with an aromatic ring structure on the surface, and a large number of new heterogeneous interfaces are formed between the modified carbon fiber and the aromatic ring grafted layer, as well as between the aromatic ring molecules. Under the action of the alternating electromagnetic field, significant interface polarization loss can be generated. At the same time, the polar groups in the aromatic ring grafted layer structure will also cause dipole orientation polarization relaxation under the action of the electromagnetic field. The polarization effect causes the restricted charges and polar dipoles at the interface to be unable to fully follow the changes in the high-frequency electromagnetic field. Its delayed response process will continuously convert the energy of the electromagnetic field into heat energy and dissipate it, while maintaining the electromagnetic shielding performance of the modified carbon fiber. Significantly reduce the secondary reflection of electromagnetic waves.
[0020] The surface of the modified carbon fiber of the present invention is covered with a dense metal plating layer, and the sulfide bonds in polyphenylene sulfide also have good coordination ability, which can significantly improve the bonding force between the polyphenylene sulfide-based outer sheath and the modified carbon fiber wrapped around the outside of the wire core, effectively reducing the relative sliding and micro-wear between the modified carbon fiber and the outer sheath during vibration, thereby effectively reducing the friction damage to the data connection harness of new energy vehicles during the vibration process of vehicle operation. DETAILED DESCRIPTION
[0021] The following is a clear and complete description of the technical solutions of the embodiments of this application. Obviously, the embodiments described are part of the embodiments of this application, not all of them. Based on the embodiments in this specification, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection requested by this application.
[0022] The sources of all raw materials in the present invention are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0023] Example 1:
[0024] A method for preparing a new energy vehicle data connection harness comprises the following steps: The first step: use a Soxhlet extractor to remove the sizing agent on the surface of the carbon fiber. The extraction solvent is acetone, the extraction temperature is 40°C, and the extraction time is 24h. After the extraction, take out the carbon fiber and wash it with anhydrous ethanol and deionized water in turn, and then dry it. Then, 80g of extracted and dried carbon fiber, 5g of silver nitrate, 80g of potassium persulfate, and 2000g of deionized water are mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, stir at a temperature of 70°C for 4h. After the reaction is completed, filter out the solid and wash it with anhydrous ethanol and deionized water in turn, and then dry it to obtain oxidized carbon fiber.
[0025] The second step: 75g of oxidized carbon fiber, 15g of silane coupling agent KH-560, and 750g of toluene were mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction was carried out at a temperature of 60°C for 16 hours. After the reaction was completed, the oxidized carbon fiber was filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried. Then, 75g of the reacted and dried oxidized carbon fiber, 25g of 4,4'-diaminodiphenyl sulfide, and 750g of toluene were mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction was carried out at a temperature of 30°C for 4 hours. After the reaction was completed, the oxidized carbon fiber was filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried to obtain functionalized carbon fiber.
[0026] Step 3: Immerse the functionalized carbon fiber in a 0.1g / L palladium chloride solution for 2 minutes and then add it to the aqueduct. Each liter of plating solution in the aqueduct contains 25g nickel sulfate, 12g dimethylamine borane, 40g sodium citrate, and the remainder is 3% ammonia water. The plating solution is preheated to 70°C and the nickel plating time is 60min. After the nickel plating is completed, the functionalized carbon fiber is taken out and washed with deionized water and dried. Then, it is heated to 200°C under nitrogen protection and kept warm for 120min to obtain modified carbon fiber.
[0027] Step 4: Mix 150g of glass fiber, 15g of silane coupling agent KH-560, and 1000g of toluene in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. Turn on the magnetic stirring and react at a temperature of 60°C for 12h. After the reaction is completed, filter out the glass fiber and wash it with anhydrous ethanol and deionized water in sequence, and then dry it to obtain modified glass fiber.
[0028] Step 5: Wrap the modified carbon fiber around the wire core, and mix 500g of polyphenylene sulfide, 100g of nylon 66, 50g of ethylene-methyl methacrylate copolymer, 150g of modified glass fiber, 30g of polytetrafluoroethylene powder, 2g of antioxidant 1010, and 1g of antioxidant 168, and add them into a twin-screw extruder. After melt extrusion at a temperature of 300°C, wrap it around the outside of the wire core wrapped with the modified carbon fiber to obtain a new energy vehicle data connection harness.
[0029] Example 2:
[0030] A method for preparing a new energy vehicle data connection harness comprises the following steps: The first step: use a Soxhlet extractor to remove the sizing agent on the surface of the carbon fiber. The extraction solvent is acetone, the extraction temperature is 60°C, and the extraction time is 12h. After the extraction, take out the carbon fiber and wash it with anhydrous ethanol and deionized water in turn, and then dry it. Then, 100g of extracted and dried carbon fiber, 8g of silver nitrate, 100g of potassium persulfate, and 2500g of deionized water are mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, stir at a temperature of 80°C for 3h. After the reaction is completed, filter out the solid and wash it with anhydrous ethanol and deionized water in turn, and then dry it to obtain oxidized carbon fiber.
[0031] The second step: 90g of oxidized carbon fiber, 18g of silane coupling agent KH-560, and 900g of toluene were mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction was carried out at a temperature of 100°C for 8h. After the reaction was completed, the oxidized carbon fiber was filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried. Then, 90g of the reacted and dried oxidized carbon fiber, 35g of 4,4'-diaminodiphenyl sulfide, and 900g of toluene were mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction was carried out at a temperature of 60°C for 2h. After the reaction was completed, the oxidized carbon fiber was filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried to obtain functionalized carbon fiber.
[0032] Step 3: Immerse the functionalized carbon fiber in a 0.5g / L palladium chloride solution for 1 minute and then add it to the aqueduct. Each liter of plating solution in the aqueduct contains 40g nickel sulfate, 20g sodium hypophosphite, 60g sodium citrate, and the remainder is 5% ammonia water. The plating solution is preheated to 90°C and the nickel plating time is 20min. After the nickel plating is completed, the functionalized carbon fiber is taken out and washed with deionized water and dried. Then, it is heated to 300°C under nitrogen protection and kept warm for 40min to obtain modified carbon fiber.
[0033] Step 4: Mix 250g of glass fiber, 25g of silane coupling agent KH-560, and 2500g of toluene in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. Turn on the magnetic stirring and react at a temperature of 100°C for 6h. After the reaction is completed, filter out the glass fiber and wash it with anhydrous ethanol and deionized water in sequence, and then dry it to obtain modified glass fiber.
[0034] Step 5: Wrap the modified carbon fiber around the wire core, and mix 600g of polyphenylene sulfide, 200g of nylon 66, 80g of ethylene-methyl methacrylate copolymer, 250g of modified glass fiber, 60g of polytetrafluoroethylene powder, 6g of antioxidant 1035, and 4g of sodium hypophosphite, and add them into a twin-screw extruder. After melt extrusion at a temperature of 290°C, wrap it around the outside of the wire core wrapped with the modified carbon fiber to obtain a new energy vehicle data connection harness.
[0035] Example 3:
[0036] A method for preparing a new energy vehicle data connection harness comprises the following steps: The first step: Use a Soxhlet extractor to remove the sizing agent on the surface of the carbon fiber. The extraction solvent is acetone, the extraction temperature is 50°C, and the extraction time is 18h. After the extraction, take out the carbon fiber and wash it with anhydrous ethanol and deionized water in turn and then dry it. Then, 90g of extracted and dried carbon fiber, 6.5g of silver nitrate, 90g of potassium persulfate, and 2250g of deionized water are mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, stir at a temperature of 75°C for 3.5h. After the reaction is completed, filter out the solid and wash it with anhydrous ethanol and deionized water in turn and then dry it to obtain oxidized carbon fiber.
[0037] The second step: 82.5g of oxidized carbon fiber, 16.5g of silane coupling agent KH-560, and 825g of toluene were mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction was carried out at a temperature of 80°C for 12h. After the reaction, the oxidized carbon fiber was filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried. Then, 82.5g of the reacted and dried oxidized carbon fiber, 30g of 4,4'-diaminodiphenyl sulfide, and 825g of toluene were mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction was carried out at a temperature of 45°C for 3h. After the reaction was completed, the oxidized carbon fiber was filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried to obtain functionalized carbon fiber.
[0038] Step 3: Immerse the functionalized carbon fiber in a 0.3g / L palladium chloride solution for 1.5 minutes and then add it to the aqueduct. Each liter of plating solution in the aqueduct contains 32.5g nickel sulfate, 16g dimethylamine borane, 50g sodium malate, and the remainder is 4% ammonia water. The plating solution is preheated to 80°C and the nickel plating time is 40 minutes. After the nickel plating is completed, the functionalized carbon fiber is taken out and washed with deionized water and dried. Then, it is heated to 250°C under nitrogen protection and kept warm for 80 minutes to obtain modified carbon fiber.
[0039] Step 4: 200g of glass fiber, 20g of silane coupling agent KH-560, and 1750g of toluene were mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, the reaction was carried out at a temperature of 80°C for 9h. After the reaction was completed, the glass fiber was filtered out and washed with anhydrous ethanol and deionized water in sequence and then dried to obtain modified glass fiber.
[0040] Step 5: Wrap the modified carbon fiber around the wire core, and mix 550g of polyphenylene sulfide, 150g of nylon 66, 65g of ethylene-methyl methacrylate copolymer, 200g of modified glass fiber, 45g of polytetrafluoroethylene powder, 4.5g of antioxidant 1010, and 2g of sodium hypophosphite, and add them into a twin-screw extruder. After melt extrusion at a temperature of 295°C, wrap it around the outside of the wire core wrapped with the modified carbon fiber to obtain a new energy vehicle data connection harness.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that the oxidized carbon fibers are not functionalized, and the other conditions and preparation steps remain unchanged.
[0042] A method for preparing a new energy vehicle data connection harness comprises the following steps: The first step: use a Soxhlet extractor to remove the sizing agent on the surface of the carbon fiber. The extraction solvent is acetone, the extraction temperature is 40°C, and the extraction time is 24h. After the extraction, take out the carbon fiber and wash it with anhydrous ethanol and deionized water in turn, and then dry it. Then, 80g of extracted and dried carbon fiber, 5g of silver nitrate, 80g of potassium persulfate, and 2000g of deionized water are mixed in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. After turning on the magnetic stirring, stir at a temperature of 70°C for 4h. After the reaction is completed, filter out the solid and wash it with anhydrous ethanol and deionized water in turn, and then dry it to obtain oxidized carbon fiber.
[0043] Step 2: Immerse the oxidized carbon fiber in a 0.1g / L palladium chloride solution for 2 minutes and then add it to the aqueduct. Each liter of plating solution in the aqueduct contains 25g of nickel sulfate, 12g of dimethylamine borane, 40g of sodium citrate, and the remainder is 3% ammonia water. The plating solution is preheated to 70°C and the nickel plating time is 60min. After the nickel plating is completed, the oxidized carbon fiber is taken out and washed with deionized water and dried. Then, it is heated to 200°C under nitrogen protection and kept warm for 120min to obtain modified carbon fiber.
[0044] Step 3: Mix 150g of glass fiber, 15g of silane coupling agent KH-560, and 1000g of toluene in a reaction bottle equipped with a condenser, a thermometer, and a magnetic stirring rotor. Turn on the magnetic stirring and react at a temperature of 60°C for 12h. After the reaction is completed, filter out the glass fiber and wash it with anhydrous ethanol and deionized water in sequence, and then dry it to obtain modified glass fiber.
[0045] Step 4: Wrap the modified carbon fiber around the wire core, and mix 500g of polyphenylene sulfide, 100g of nylon 66, 50g of ethylene-methyl methacrylate copolymer, 150g of modified glass fiber, 30g of polytetrafluoroethylene powder, 2g of antioxidant 1010, and 1g of antioxidant 168, and add them into a twin-screw extruder. After melt extrusion at a temperature of 300°C, wrap it around the outside of the wire core wrapped with the modified carbon fiber to obtain a new energy vehicle data connection harness.
[0046] Experimental Example 1 The new energy vehicle data connection harnesses in Examples 1 to 3 and Comparative Example 1 were subjected to shielding performance tests, vibration durability tests, and secondary reflection tests, respectively. The test results are shown in Table 1: Electromagnetic shielding performance test and vibration durability test: Tested in accordance with the national standard GB / T 37133-2018 "Technical Requirements for High-Voltage and High-Current Wiring Harnesses and Connectors for Electric Vehicles".
[0047] Secondary reflection test: Refer to the national standard GB / T 30139-2013 "General technical conditions for shielding effectiveness of industrial electromagnetic shielding fabrics" to test the absorption ratio of each component modified carbon fiber.
[0048] Table 1
[0049] It can be seen from Table 1 that the modified carbon fibers in Examples 1 to 3 significantly improve the coverage and density of the nickel plating after functional modification, and the nickel plating and the carbon fibers have better bonding ability, thereby having better shielding effectiveness and being less susceptible to vibration damage. The aromatic ring grafted layer grafted between the nickel plating and the carbon fibers effectively improves the absorption of electromagnetic waves by the modified carbon fibers and reduces secondary electromagnetic wave reflection pollution.
[0050] The above embodiments are intended only to facilitate understanding of the methods and core concepts of the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein, but is intended to be construed in the widest manner consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a new energy vehicle data connection harness, characterized in that: The following steps are involved: The carbon fiber is stripped of its surface sizing agent and oxidized to obtain oxidized carbon fiber. A silane coupling agent is then grafted onto the surface of the oxidized carbon fiber and reacted with 4,4'-diaminodiphenyl sulfide to obtain functionalized carbon fiber. The functionalized carbon fiber is then nickel-plated on its surface and heat-treated to obtain modified carbon fiber. The modified carbon fiber is wrapped around the wire core, and a polyphenylene sulfide-based composite material is melt-extruded and coated on the outside of the wire core wrapped with the modified carbon fiber to obtain a new energy vehicle data connection harness.
2. The method for preparing a new energy vehicle data connection harness according to claim 1, characterized in that: The preparation steps of oxidized carbon fiber are as follows: The sizing agent on the surface of the carbon fiber is removed, the extraction solvent is acetone, the extraction temperature is 40-60°C, the extraction time is 12-24h, and the extracted carbon fiber, silver nitrate, potassium persulfate and deionized water are mixed and reacted at a temperature of 70-80°C to obtain oxidized carbon fiber.
3. The method for preparing a new energy vehicle data connection harness according to claim 1, characterized in that: The preparation steps of functionalized carbon fibers are as follows: The oxidized carbon fibers, silane coupling agent KH-560 and toluene are mixed and reacted at a temperature of 60 to 100° C. The oxidized carbon fibers, 4,4'-diaminodiphenyl sulfide and toluene after the reaction are mixed and reacted at a temperature of 30 to 60° C. to obtain functionalized carbon fibers.
4. The method for preparing a new energy vehicle data connection harness according to claim 1, characterized in that: The preparation steps of modified carbon fiber are: The functionalized carbon fiber is immersed in a palladium chloride solution and then added to a plating solution containing a nickel source, a reducing agent, a complexing agent and ammonia water for nickel plating, and the plating solution is preheated. After the nickel plating is completed, the functionalized carbon fiber is taken out and heat-treated under nitrogen protection to obtain a modified carbon fiber.
5. The method for preparing a new energy vehicle data connection harness according to claim 1, characterized in that: The preparation steps for the new energy vehicle data connection harness are as follows: The modified carbon fiber is wrapped around the outside of the wire core, and polyphenylene sulfide, nylon 66, a compatibilizer, modified glass fiber, polytetrafluoroethylene powder, and an antioxidant are mixed, melt-extruded, and then coated on the outside of the wire core wrapped with the modified carbon fiber to obtain a new energy vehicle data connection harness.
6. The method for preparing a new energy vehicle data connection harness according to claim 4, characterized in that: The nickel source is nickel sulfate, the reducing agent is at least one of dimethylamine borane and sodium hypophosphite, and the complexing agent is at least one of sodium citrate and sodium malate.
7. The method for preparing a new energy vehicle data connection harness according to claim 5, characterized in that: The preparation steps of modified glass fiber are: The modified glass fiber is obtained by mixing glass fiber, silane coupling agent KH-560 and toluene and reacting them at a temperature of 60-100 DEG C.
8. The method for preparing a new energy vehicle data connection harness according to claim 5, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 1035, sodium hypophosphite, and antioxidant 168.
9. The method for preparing a new energy vehicle data connection harness according to claim 5, characterized in that: The compatibilizer is ethylene-glycidyl methacrylate copolymer.
10. The method for preparing a new energy vehicle data connection harness according to claim 5, characterized in that: The temperature condition for melt extrusion is 290 to 300°C.
Citation Information
Patent Citations
Preparation method of modified carbon fiber, antistatic composite material and preparation method of antistatic composite material
CN111719314A
Carbon fiber surface grafted two-dimensional network structure reinforced polyether-ether-ketone composite material and preparation method thereof
CN112457629A
Polyphenylene sulfide linear oligomer grafted modified carbon fiber as well as preparation method and application thereof
CN114318878A
Fire-resistant shielding type marine control cable
CN115547544A
Multi-layer structure cable with high thermal conductivity
CN119626655A